SOSIALISASI PENATAAN PERKAMPUNGAN KUMUH - Usman, Ahmad (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2024)
Socialization of slum upgrading plays an important role in making people aware of the need to take part in beautifying the area where they live. This service aims to analyze the socialization of slum upgrading in Oimbo Village, Bima City, conducted by a team of lecturers from Mbojo University, Bima. There are several stages of socialization as a form of awareness, namely: (a) about slums and their characteristics and indicators, (b) things that need to be done in order not to be categorized as a slum, (c) the need for community participation in the arrangement of slum villages, (d) the role of the government as a facilitator. This socialisation is the first step in raising community awareness and there will be further socialisation. In conclusion, community awareness plays a vital role in creating through socialization programs from government agencies, the private sector, and entrepreneurs